Health-Related Quality of Life Burden Among Adults with Vitiligo: Relationship to Disease Severity and Disease Location - David Rosmarin; Ahmed M. Soliman; James Piercy; Simran Marwaha; Peter Anderson; Heidi S. Camp (Adis, Springer Healthcare, 2024)
Abstract Introduction Vitiligo was historically regarded as a cosmetic disorder; however, it is an autoimmune disease. As a visible condition, it affects patient well-being. We assessed the impact of disease severity, lesion location, and body surface area (BSA) affected on patient health-related quality of life (HRQoL). Methods Retrospective data were from the Adelphi Real World Vitiligo Disease Specific Programme: a cross-sectional survey of physicians and their patients with vitiligo (10/2021-07/2022). Patient-reported outcomes were assessed by the Vitiligo-Specific Quality of Life Instrument (VitiQoL), Hospital Anxiety and Depression Scale (HADS), and EQ-5D-5L. The Work Productivity and Impairment Questionnaire (WPAI) questionnaire was used to assess disease-related impairment of daily activities. Data were stratified by physician-reported disease severity, presence/absence of vitiligo on the face, and BSA percentage affected. Results In total, 1388 patients were included. Mean (SD) VitiQoL, HADS depression, and anxiety scores were higher for those with severe disease [40.5 (26.1), 5.2 (4.4), and 6.8 (4.7)] than those with mild [24.8 (18.8), 3.6 (3.8), 4.2 (3.8)] or moderate [27.1 (22.6), 3.8 (4.5), 4.3 (4.4)] disease. Patients with face affected reported higher VitiQoL [30.0 (22.3) versus 23.2 (19.3)], and HADS scores [depression, 4.3 (4.3) versus 3.2 (3.9); anxiety, 5.0 (4.3) versus 3.8 (3.9)] than those without. Patients with ≥ 5% BSA affected had higher VitiQoL, depression and anxiety scores [27.9 (21.8), 4.0 (4.4), and 4.5 (4.2)] than those with 0-5% [24.6 (19.7), 3.4 (3.7), and 4.3 (4.1)]. Patients with severe vitiligo, facial lesions, or ≥ 5% BSA reported higher activity impairment. Mean EQ-5D-5L-utility score was approximately 0.9 regardless of disease severity or total BSA affected. Conclusions These data demonstrate the impact disease severity can have on HRQoL and daily activities for patients with vitiligo. Lesions that are more severe, on the face, or covering a greater BSA are more often associated with poorer outcomes and activity impairment. These data also highlight the potential insensitivity of commonly used HRQoL measures and a need for more sensitive disease-specific measures.